2019
DOI: 10.4269/ajtmh.18-0896
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene in Restaurants and among Street Food Vendors in Bangladesh

Abstract: Poor hand hygiene and food handling put consumers of restaurant and street food at risk of enteric disease, especially in low-income countries. This study aimed to collect hygiene indicators from a nationally representative sample of restaurants and street food vendors. The field team collected data from 50 rural villages and 50 urban administrative units (mahallas). We explored restaurant service staff, cook, and food vendor hygiene practices (N = 300 restaurants and 600 street food vendors), by observing hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
6
22
0
1
Order By: Relevance
“…The IBM-WASH model was also applied to evaluate a WASH intervention for reducing improper trash disposal in communal toilets [49] and a combination of various interventions, such as hygiene education, provision of hardware, and WASH events [50]. Furthermore, the IBM-WASH model has been used to understand the opportunities and challenges for a specific behavior, such as hygiene practices in food preparation [51,52]. The IBM-WASH model has also been applied in South America to evaluate WASH technologies, such as drinking water chlorination [53] and baby bottle disinfection [54], as well as to understand behavior regarding latrine use [55].…”
Section: Factors Of the Ibm-wash Model Relevant For Sustainable Behaviormentioning
confidence: 99%
“…The IBM-WASH model was also applied to evaluate a WASH intervention for reducing improper trash disposal in communal toilets [49] and a combination of various interventions, such as hygiene education, provision of hardware, and WASH events [50]. Furthermore, the IBM-WASH model has been used to understand the opportunities and challenges for a specific behavior, such as hygiene practices in food preparation [51,52]. The IBM-WASH model has also been applied in South America to evaluate WASH technologies, such as drinking water chlorination [53] and baby bottle disinfection [54], as well as to understand behavior regarding latrine use [55].…”
Section: Factors Of the Ibm-wash Model Relevant For Sustainable Behaviormentioning
confidence: 99%
“…Another study showed that 2.5% of samples tested positive for Escherichia coli in food taken from meat sold by food colonizers [10]. Bangladesh National Hygiene Baseline Survey research as traders only know about 37% of cleanliness, potentially triggering foodborne disease [11]. In Saudi Arabia, the foodborne disease outbreak has infected catering food vendors, amounting to 1.26% of the 1000 catering food sellers [12].…”
Section: Issn: 2252-8806 mentioning
confidence: 99%
“…Researchers around the world have similar interests in working on hygiene and safety practices related to street food near their places. For instance, some latest research works have been completed in countries such as China (Dai, Zhong, & Scott, 2019), Bangladesh (Nizame, Alam, Masud, Shoab, Opel, Islam, Luby, & Unicomb, 2019), Ghana (Ghartey, Adu-Oppong, & Doku, 2019), Ethiopia (Tadesse, Mitiku, Teklemariam, & Marami, 2019), and Namibia (Shiningeni, Chimwamurombe, Shilangale, & Misihairabgwi, 2019) addressing food hygiene, safety and microbial quality found in the street food. One study was completed in Florida, USA relating to regulations and its challenges for street food inspection (Okumus & Sonmez, 2019).…”
Section: Current Research Trend On Street Foodmentioning
confidence: 99%